Frontiers Reimagined- Art that connects us- 44 countries | 25 countries : 56th International Art Exhibition- La Biennale di Venezia 2015 - Fathi, Golnaz; Green, Denise; Ibrahim, Georges Fikry; Lipi, Tayeba Begum; Massoudy, Hassan; Muniz, Vik; Qadri, Sohan; Rauschenberg, Robert; Tworkov, Jack; Yasuda, Robert; Tagore Foundation International (Venice; Marsilio Editori, 2015)
Frontiers Reimagined examines the results of these cultural entanglements through the work of more than 40 painters, sculptors, photographers.
English
Keywords: Biennial Collateral event catalog; N4390-5098 Visual Arts- Exhibitions; Italy